Relationship between frontal systems and extreme precipitation over southern South America - Solari, Florencia Ilusión (2022)
The relationship between frontal systems and extreme precipitation events over southern South America is analyzed for the austral winter (May--August) and spring (September-December), on a 39-year period spanning from 1979 to 2017. Daily gridded data from the CPC Global Unified Precipitation dataset and the ERA5 reanalysis is employed. Fronts are identified by means of an objective front index (FI) that takes into account both dynamic (cyclonic vorticity) and thermodynamic (thermal contrast) characteristics. Extreme precipitation is characterized by the seasonal 95th percentile.Fronts occur in midlatitudes in about 10% of the days but there is a seasonal shift with larger occurrence frequencies located at southern latitudes in spring compared to winter. Front intensity-calculated as the seasonal mean of FI-is stronger in winter than in spring but the spatial pattern is similar on both seasons. Fronts explain about 50% of extreme precipitation on winter and 40% on spring; the percentage of total precipitation explained by fronts is lower but the spatial distribution is similar.Comparison between fronts that produce precipitation and the ones associated with extreme precipitation revealed that the latter are more intense on average. Fronts that produce extreme precipitation have a stronger dynamic forcing (i.e. higher cyclonic vorticity values) and a higher moisture availability (higher specific humidity anomaly). These two characteristics are the most promising for enhancing extreme precipitation events forecast.